Recycled concrete aggregate as a road base material. (May 2019) - Giwangkara, G. G.; Mohamed, A.; Khalid, N. H. A.; Nor, H. M.; Hainin, M. R.; Jaya, R. P.; Sani, W. N. H. M.; Ismail, C. R.; Aziz, M. M. A.
Abstract: Natural crushed aggregate (NCA) is the most common material for aggregate throughout the world. The consumption of the NCA itself is rising up through the years. Concrete structures and road construction are some of the most consuming aggregate material, especially NCA. Therefore, aggregate such as recycled concrete aggregate (RCA) has become an alternative material for some particular civil construction. The implementation of RCA as road construction material has been raised for a long time ago especially in road base layer. Road base layer as foundation for road pavement must provide an adequate strength to hold the working load on the pavement surface. RCA is more heterogeneous material compared to NCA as the RCA contain many substances, such as aggregate, cement, sand, and some additive substances. Hence, it effects the strength of the RCA as construction material. In this paper, the properties of the RCA are investigated to get the characteristic of the aggregate. Density, water absorption, aggregate crushing value (ACV), compaction, and penetration test (CBR) were conducted in this research. An improvement by using plastic strips as addition also proposed to strengthen the RCA as road base material.